Illegal parcelling in Cordoba (Spain) - López-Casado, David (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2020)
Illegal parcellings are a unique case within urban sprawl processes. They are characterised by originating against urban planning and by a lack of basic infrastructure. It is a phenomenon that has not been studied in much depth, and its typological aspect has been the least discussed element. This article analyses the illegal parcellings in the municipality of Cordoba, Spain, where their area has reached 4,606.88 hectares-this, compared to the slightly more than 2,800 hectares occupied by the consolidated city, gives an idea of the significance of the process. The main objective is therefore to present its territorial scope and, secondly, to propose a methodology for its typological classification. Research shows that this issue is important for a correct assessment of the phenomenon and that it must be addressed appropriately by the relevant administrations.
Keywords: geografija naselij; ilegalna stanovanjska gradnja; illegal housing development; mesta; settlement geography; Spain; suburbanisation; suburbanizacija; Španija; urban geography